Foam in pharmaceutical and medical applications. (December 2019) - Parsa, Maryam; Trybala, Anna; Malik, Danish Javed; Starov, Victor
Abstract: Topical foams are an attractive and promising delivery system for cosmetic, pharmaceutical and medical applications due to their beneficial properties, ease of application and enhanced patients' acceptability/compliance. Below the recent developments of topical foams for cosmetic and dermal applications are reviewed, classification based on foam formulation is provided and recent assessment methods of important physical parameters of topical foam are reviewed. In spite of the increasing number of studies devoted to topical foams for dermal applications, the majority of studies have assessed the stability and structure of foam in contact with solid nonporous surfaces. Improved understanding of the destabilisation mechanisms of such foams in contact with porous surfaces, such as skin or skin-like membranes still remains elusive. The review ends with recent developments in dermal foams; considerable attention has been paid in developing novel foams for the treatment of chronic skin diseases and disorders, particularly those involving skin infections. Graphical abstract: Image 1 Highlights: Topical foams for cosmetic and dermal applications. Recent assessment methods of important physical parameters of topical foam. Topical foams in contact with skin or skin-like membranes.